O catador de resíduos sólidos recicláveis e a desigualdade social - Sandra Regina Medeiros Romancini; Ednilson Viana; Teresinha Maria Gonçalves (Ciências Sociais Unisinos)
This article discusses the exclusion/inclusion or the unequal inclusion of the catcher of solid waste you recycled in the current society, starting from research close to the dump in Içara/SC. We are looking forward to investigate also regarding the invisibility of the catcher of residues you recycled along with the society, even admitting the importance of your work for the urban cleaning, as well as legitimation that these workers undertake to the values of the modern society the measure that you face significant barriers for if they integrate the society for the work. The production of urban solid waste in levels never seen it is discussed, for being the object of work of the catcher, and also constituting in contradicion in modernety, since it comes as serious partner-environmental problem, that lacks of short term solutions.